The Analysis of Employee Workload through Subjective Workload Assessment Technique (SWAT) and Swedish Occupational Fatigue Inventory (SOFI) Methods - Dhanu Ega Sentanu; Akmal Suryadi (PT Mattawang Mediatama Solution, 2023)
This studi aims the workload level that employees have in the Marketing Department and improvement department at PT. XYZ , measurements were carried out using the SWAT (Subjective Workload Assessment Technique) and SOFI (Swedish Occupational Fatigue Inventory) methods by recognizing the level of employee workload, because the large amount of heavy workload will have an impact on work stress. Therefore, it is important to concern the related aspects so that the employees can produce an optimal output. The Repair Department employees have the highest workload value, that is in the fourth activity, namely checking vehicles which has a value of 70%. Based on the results of data processing in ten respondents of Marketing Department employees, it can be concluded that the Mental workload in the medium category is 100%. Meanwhile, the highest dimension with an average value of 3,97, namely Lack of Energy. Then, Physical Activity (Physical Exertion) with a total average of 2,66. Lack of Motivation with a total average of 1,78, Physical Discomfort with an average total of 1,53. Based on calculations on employees of the Repair Department, the SWAT percentage of 70% is included in the category of Repair is Necessary.